Analysis of the dihydrofolate reductase-thymidylate synthase gene sequences in Plasmodium vivax field isolates that failed chloroquine treatment - Kim Hyuck; Sohn Youngjoo; Sattabongkot Jetsumon; Kim Jung-Yeon; Kim Mi-A; Choi Kyung-Mi; Choi Yien-Kyoung; Kim Hyung-Hwan; Lee Won-Ja; Lee Jong-Koo; Park Han-Sook; Lee Hyeong-Woo (Malaria Journal, 2010)
Abstract Background To use pyrimethamine as an alternative anti-malarial drug for chloroquine-resistant malaria parasites, it was necessary to determine the enzyme's genetic variation in dihydrofolate reductase-thymidylate syntase (DHFR-TS) among Korean strains. Methods Genetic variation of dhfr-ts genes of Plasmodium vivax clinical isolates from patients who did not respond to drug treatment ( n = 11) in Korea were analysed. The genes were amplified using the polymerase chain reaction (PCR) with genomic DNA as a template. Results Sequence analysis showed that the open reading frame (ORF) of 1,857 nucleotides encoded a deduced protein of 618 amino acids (aa). Alignment with the DHFR-TS genes of other malaria parasites showed that a 231-residue DHFR domain and a 286-residue TS domain were seperated by a 101-aa linker region. This ORF shows 98.7% homology with the P. vivax Sal I strain (XM001615032) in the DHFR domain, 100% in the linker region and 99% in the TS domain. Comparison of the DHFR sequences from pyrimethamine-sensitive and pyrimethamine-resistant P. vivax isolates revealed that nine isolates belonged to the sensitive strain, whereas two isolates met the criteria for resistance. In these two isolates, the amino acid at position 117 is changed from serine to asparagine (S117N). Additionally, all Korean isolates showed a deletion mutant of THGGDN in short tandem repetitive sequences between 88 and 106 amino acid. Conclusions These results suggest that sequence variations in the DHFR-TS represent the prevalence of antifolate-resistant P. vivax in Korea. Two of 11 isolates have the Ser to Asn mutation in codon 117, which is the major determinant of pyrimethamine resistance in P. vivax . Therefore, the introduction of pyrimethamine for the treatment of chloroquine-resistant vivax malaria as alternative drug in Korea should be seriously considered.